Dominant in Poetic Supertextual Unit: Problem Statement - Hakobyan, Levon (Bulletin of Yerevan University H: Russian Philology, 2024)
The article for the first time raises the question of the dominant in the main forms of poetic supertextual unit - in a crown of sonnets, in a lyric cycle and in a book of poems.The most important feature of the dominant in a supertextual unit is the potential possibility of its revelation at two levels: at the level of a word image and at the level of the text.The word-image dominant is based on the cross-textual repetition of a word/phrase, that is a multiple reproduction of a lexical image or its correlates in two or more texts of a given unit.The textual dominant is a poem that most fully embodies the main idea and meaning of the supertextual whole, and represents a force field that attracts many thematically and conceptually close texts that form a supertextual unit.The ideal example of a textual dominant is the master-sonnet of a crown of sonnets, which determines the structure-forming and meaning-forming system of the whole. Textual dominants in other supertextual forms can approach only to a greater or lesser extent the function performed by the master-sonnet.Unlike the crown of sonnets, the ideological and conceptual component of the lyrical cycle cannot be fully expressed in one single text, since it is generated only by the interaction of all the texts of the cyclic series, therefore no text, including the dominant one, is a full-fledged embodiment of the meanings of the whole. In the cycle, the textual dominant does not perform a genre-forming function, so the presence of a textual dominant here is an optional factor. Poetic texts included in a book of poems do not have the intensity of intertextual connections that is characteristic of a lyrical cycle. The poems of one conceptual and thematic group are scattered throughout the entire space of the book of poems, forming structurally undetermined conceptual and thematic concenters. The compositional uncertainty of the concenters causes the specificity of the textual dominant in this type of book of poems. Having no other constructive function, the textual dominant in the book of poems plays an important meaning-organizing role in the concenter.
Keywords: dominant; supertextual unit; cross-textual connections; crown of sonnets; lyrical cycle; book of poems